From the lab to the field and back: the effects of need satisfaction on reconciliation among Germans and Israelis - Pesin-Michael, Gali; Ditlmann, Ruth K.; Shnabel, Nurit (Frontiers in Psychology, 2024)
Previous lab experiments supported the hypotheses of the needs-based model of reconciliation, according to which (a) when discussing historical transgressions, members of the perpetrator [victim] group experience an enhanced need for acceptance [empowerment], and (b) addressing this need (e.g., through accepting [empowering] messages by outgroup members) increases group members' willingness to reconcile with the outgroup. Heeding calls to test reconciliation theories in the field, Study 1 examined hypotheses derived from the model among German and Israeli Jewish participants (N = 143) of youth exchange programs. As expected, Germans' feelings of acceptance associated with three proxies of willingness to reconcile; namely, program satisfaction, positive outgroup attitudes, and keeping in touch with the Israeli Jews who participated in the program. Among Israeli Jewish participants, as expected, feelings of empowerment associated with program satisfaction and positive outgroup attitudes. Unexpectedly, however, keeping in touch with Germans associated with their feelings of acceptance (but not with their feelings of empowerment). A possible explanation for this finding is that keeping in touch with Germans is done mainly through social networks, where Israel's transgressions against Palestinians are more salient than during the exchange program. Study 2, a preregistered lab experiment (N = 293 Israeli Jews) supported this possibility: In the condition where their ingroup's transgressions against Palestinians were salient, participants perceived accepting messages by Germans to be more conciliatory than empowering messages; the opposite pattern emerged in the condition where their ingroup's victimization by Nazi Germans was salient. Implications for people-topeople peacebuilding interventions are discussed.